Antifungal Activity of Vanillic Acid-Grafted Chitosan Derivatives against Plant Pathogenic Fungi, Fusarium sp. - Wan Roslina, Wan Yusof; Awang Ahmad Sallehin, Awang Husaini; Enis Nadia, Md. Yusof.; Sumiyyah, Sabar (American Chemical Society, 2024)
The present work aimed to obtain chitosan derivatives with greater solubility in water, good physicochemical properties, and potent antifungal activity against plant pathogens. In this study, the modification of chitosan (CS) with vanillic acid (VA) was achieved via free radical grafting by optimizing the VA to CS ratio. The grafted CS (VA-g-CS) samples were characterized,and their antifungal activity toward Fusarium solani and Fusarium proliferatum was evaluated. All VA-g-CS samples demonstrated successful conjugation between CS and VA, with different grafting degrees, altered surface morphology, and improved water solubility. The results indicated that VA-g-CS with a mass ratio of 0.5:1 exhibited the highest content of VA (74.6 ± 1.42 mg of VAE/g) with an amino substitution percentage of 50.3 ± 0.54%. Increasing the concentration of VA-g-CS from 1.0 to 5.0 mg/mL enhanced their antifungal activity. Furthermore, VA-g-CS (0.5:1) at 5.0 mg/mL showed better antifungal activity than other grafted CS, with more than 80 and 76% inhibition against F. solani and F. proliferatum, respectively. The modification of CS with VA offers a new strategy for controlling plant pathogenic fungi.